Blind spot [large type] - Pettrey, Dani (Pettrey, Dani. Chesapeake valor, 2017)
FBI agent Declan Grey is in the chase of his life--but isn't sure exactly what he's chasing after. Threatened by a terrorist that "the wrath is coming," Grey fears something horrible is about to be unleashed on American soil. When his investigation leads him to a closed immigrant community, he turns to Tanner Shaw to help him. She's sought justice for refugees and the hurting around the world, and if there's anyone who can help him, it's Tanner.